The effects of overtraining protocol on markers of oxidative stress and inflammation - Amriansyah Syetiawinanda; Muchsin Doewes; Bambang Purwanto; Soetrisno Soetrisno; Agus Kristiyanto; Eti Poncorini Pamungkasari (Universitas Udayana dan Diaspora Taipei Medical University, 2025)
Background: Overtraining can elevate reactive oxygen species (ROS), suppress endogenous antioxidant activity, and trigger systemic inflammation. Monitoring oxidative stress and inflammation is essential to prevent muscle damage. This study aimed to examine the effects of an overtraining protocol on oxidative stress and inflammatory markers MDA, IL-6, NO, and SOD in male Wistar rats. Methods: The experimental was conducted over two weeks using male Wistar rats at the Bioscience Institute Laboratory, Universitas Brawijaya, Malang, Indonesia as a preliminary study. Three rats were examined to assess the effects of overtraining on MDA, IL-6, NO, and SOD levels. Observations were made one day after overtraining protocol for the intervention group value (KP) and six weeks after overtraining for the control group value (K1). Results: Three male rats underwent an overtraining protocol, and blood samples were collected one day post-overtraining (KP) to assess MDA, IL-6, NO, and SOD levels. The mean values at KP were MDA: 370.3 ± 10.3, IL-6: 5.9 ± 0.7, NO: 61.0 ± 8.4, and SOD: 0.05 ± 0.03. At six weeks post-overtraining (K1), MDA (192.8 ± 10.3), IL-6 (3.3 ± 1.9), and NO (41.7 ± 21.6) levels were lower, while SOD (0.3 ± 0.2) was higher compared to KP. Conclusion: Overtraining can elevate ROS and inflammatory responses, as indicated by increased MDA, IL-6 levels, and NO, along with reduced SOD expression.